Numerical Solution of Casson Fluid Flow Under Viscous Dissipation - Zainuddin, Muhammad Fakhrul Syazwan; Mohamad, Mahathir (Enhanced Knowledge in Sciences and Technology, 2025)
The Casson fluid model plays a critical role in describing non-Newtonian fluid behaviour, particularly in systems where Newtonian assumptions are inadequate. This study focuses on investigating the influence of viscous dissipation on the flow characteristics of Casson fluid under boundary layer conditions. The governing nonlinear partial differential equations are transformed into ordinary differential equations using the Similarity Transformation. These equations are then solved numerically using the Fourth Order Runge-Kutta (RK4) method in conjunction with the Shooting Method. The results reveal how viscous dissipation significantly alters velocity and temperature profiles within the fluid flow, influencing thermal boundary thickness and energy transfer rates. Graphical representations illustrate these effects, offering deeper insights into the dynamics of non-Newtonian fluids under dissipative conditions. The study establishes the importance of considering viscous dissipation for accurate modelling of Casson fluid flow, enhancing its applicability to industrial, medical, and engineering systems.